Crystal structures of two alkaline earth (M = Ba and Sr) dimanganese(II) iron(III) tris(orthophosphates) - Ghaleb Alhakmi; Abderrazzak Assani; Mohamed Saadi; Lahcen El Ammari (Acta Crystallographica Section E: Crystallographic Communications, 2017)
Two new orthophosphates, BaMn2Fe(PO4)3 [barium dimanganese(II) iron(III) tris(orthophosphate)] and SrMn2Fe(PO4)3 [strontium dimanganese(II) iron(III) tris(orthophosphate)], were synthesized by solid-state reactions. They are isotypic and crystallize in the orthorhombic system with space group type Pbcn. Their crystal structures comprise infinite zigzag chains of edge-sharing FeO6 octahedra (point group symmetry .2.) and Mn2O10 double octahedra running parallel to [001], linked by two types of PO4 tetrahedra. The so-formed three-dimensional framework delineates channels running along [001], in which the alkaline earth cations (site symmetry .2.) are located within a neighbourhood of eight O atoms.